A 2x4 Element Rectangular H-Slot Array Microstrip Antenna Rectifier for Harvesting Electromagnetic Energy at 2.4 GHz Frequency - Darmono, Hendro; Koesmarijanto, Koesmarijanto; Suharto, Nugroho; Ratnawati, Yani; Cahyono , Agung Dwi (Jurnal Jaringan Telekomunikasi, 2023)
This research aims to develop an energy capture system, specifically an antenna rectifier. The chosen antenna for this purpose is a microstrip antenna operating at a frequency of 2.4 GHz, utilizing a 2x4 array configuration to enhance the collection of electromagnetic waves emitted by an Access Point. To enhance the rectifier's voltage-doubling capability, the design incorporates three distinct levels: level 8, level 12, and level 14. Experimental results from implementing the 2x4 rectangular H-Slot array microstrip antenna rectifier demonstrate its capacity to convert incoming AC waves from the antenna into DC voltage. During the implementation phase, the rectenna harvesting system exhibits notable outcomes. The most significant outcome is observed in the 14th-level rectifier circuit, yielding a conversion of 101.98 mV when positioned 50 cm away from the wireless source or access point. This voltage reading diminishes to 49.148 mV at 200 cm. In the 12th-level rectifier circuit, the values are 64.8 mV at 50 cm and 39.08 mV at 200 cm. Furthermore, the 8th level circuit generates 24.72 mV at 50 cm and 11.4 mV at 200 cm. Evidently, the proximity of the testing distance correlates with the magnitude of the produced voltage.